Numerical simulation of steel I-shaped beams using a fiber-based damage accumulation model. (June 2017) - Bosco, Melina; Tirca, Lucia
Abstract: This study proposes a fiber-based hinge damage accumulation model that is able to replicate the nonlinear response of I-shaped beams of steel moment resisting frames. The model is developed in OpenSees and consists of a beam with hinges element with fiber cross-section discretization within the plastic hinge zone. Among various plastic hinge integration methods, the modified Gauss-Radau integration scheme was selected. The proposed model incorporates strength and stiffness deterioration caused by flange local buckling of I-shaped beams which is simulated by assigning a calibrated low-cycle fatigue material model to flange fibers. In this formulation, fatigue material uses a modified rainflow cycle counting algorithm to accumulate damage based on Miner's rule. The values of fatigue material coefficients were calibrated against 16 experimental test results selected from the literature. An equation able to predict the fatigue ductility coefficient that follows a linear variation along the flange width is proposed based on regression analysis. In addition, a global damage index, DIs, defined as the ratio between the number of fibers that reach fatigue and the number of fibers within the top and bottom flanges of I-shaped cross-section, is developed and a global damage index value associated with the onset of beam failure, labelled DIs(80%)prop is proposed. An application comprising a single-storey, one-bay steel MRF is carried out in OpenSees, which validates the proposed beam model as computationally effective under cyclic quasi-static and dynamic loading. Highlights: A fiber-based hinge damage accumulation model for I-shaped beams of MRFs is proposed. A low-cycle fatigue model able to simulate the effect of flange local buckling is developed. A value of global damage index is set to predict the failure of I-beam under dynamic loads. The proposed model is computational effective when the MRF is subjected to real records.